Healthcare-Associated Infection Prevention Interventions for Neonates in Resource-Limited Settings - Dramowski, Angela; Aucamp, Marina; Beales, Emily; Bekker, Adrie; Cotton, Mark Frederic; Fitzgerald, Felicity C.; Labi, Appiah-Korang; Russell, Neal; Strysko, Jonathan; Whitelaw, Andrew; Coffin, Susan (Frontiers in Pediatrics, 2022)
Healthcare-associated infections (HAI) and antimicrobial-resistant (AMR) infections are leading causes of neonatal morbidity and mortality, contributing to extended hospital stay and increased healthcare costs. Although the burden and impact of HAI/AMR in resource-limited neonatal units is substantial, there are few HAI/AMR prevention studies from these settings. We reviewed the mechanism of action and evidence supporting HAI/AMR prevention interventions, including care bundles, for hospitalized neonates in low- and middle-income countries.